Effects of Postharvest Coatings and Heat Treatment on Quality of Stored Pineapple Fruits - Othman, Zaulia (2008)
Studies on the effect of postharvest treatments (surface coating, heat, and, combination of surface coating and heat treatments) on the changes in physico-chemical characteristics, rate of respiration, diseases and physiological disorder of fresh N36 and Gandul pineapples during storage at 10 ± 10C were carried out. Studies on the effect of various surface coating emulsion (paraffin, palm oil and Semperfresh) showed that palm oil was effective in maintaining the skin firmness, prolonging shelf life, significantly (p <0.05) increasing SSC and subsequently receiving the highest scores in appearance, colour and texture in sensory evaluation of N36 pineapples. Palm oil treatment significantly (p <0.05) reduced ascorbic acid (AA) content, fructose, sucrose and total sugar for Gandul pineapples. Paraffin retarded the ripening, significantly (p <0.05) increased pH, SSC:TA ratio, fructose and glucose content and scores for odour, and sourness but reduced SSC of N36 pineapples. In Gandul pineapples, paraffin significantly (p <0.05) increased AA, TA and fructose content but reduced pH. All the surface treatments were able to significantly reduce weight loss, except for Semperfresh. Semperfresh increased fructose and glucose content and reduced SSC of N36 pineapples. In Gandul pineapples, Semperfresh significantly lowered (p <0.05) pH, fructose, sucrose and total sugar content. CO2 production can only be reduced by paraffin treatment in Gandul pineapple. Heat treatment (HT) (38-420C for 24 hours) and combination of heat and surface coating treatment (CHT) were applied to N36 and Gandul pineapples before storage at 10 ± 1°C, 85 – 88% relative humidity. HT reduced internal browning (IB) and decayed fruit, promoted colour development on skin and pulp but increased weight loss in both cultivars. The positive effects of HT were more significant (p <0.05) in Gandul cultivar than N36 cultivar. HT significantly increased (p <0.05) fructose, glucose, SSC and AA in Gandul cultivar and sensory scores of N36 cultivar. CHT significantly reduced (p <0.05) weight loss during heating and increased SSC:TA ratio in both cultivars. It also increased (p <0.05) total sugar and SSC in N36 cultivar, and increased the sensory taste for Gandul cultivar. HT did not affect CO2 production of N36 and Gandul pineapples stored at low temperature.